The Reflection of Minimalism on Cinematic Spaces and a Yasujiro Ozu Film Tokyo Story - Öztürk, Belis (Journal of Interior Design and Academy, 2024)
The minimalism movement emerged in the 1960s in America and emphasized simplicity and unadorned expression in art. In cinema, minimalism minimizes the use of cinematic devices to focus on realism. Notable figures include Yasujiro Ozu and Robert Bresson. Ozu's films, such as Tokyo Story, prioritize clarity and simplicity, inviting deep thought. The use of spaces filled with mundane elements of everyday life and a simple color palette enhances the sense of reality and reflects the inner worlds of the characters. Emphasizing real life and human relationships, minimalist cinema avoids artificial structures and brings viewers closer to emotional experiences. This study examines Ozu's minimalist approach to cinematic language and spatial design.